ANALISIS PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN SOSIOLOGI SISWA KELAS XI IPS 1 SMA - Beti, Beti (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
The title of this thesis is "Analysis of the Application of the Model Discovery Learning in Sociology Learning for Students of Class XI IPS 1 for Public Senior High School 1 foreman". This thesis is descriptive in qualitative form. The purpose of this study was to determine the implementation of stimulation (stimulation of stimulation) in the learning of sociology of Class XI IPS 1 Senior High School 1 Mandor, the implementation of problem statements in the Sociology Learning of Class XI IPS 1 Senior High School 1 Foreman. implementation of data collection (data collection) in Sociology Learning for Students of Class XI IPS 1 State Senior High School 1 foreman, implementation of data processing in Sociology Learning Class XI IPS 1 State Senior High School 1 Mandor, implementation of verification in Sociology Learning Class Students XI IPS 1 State Senior High School 1 Mandor, and the implementation of generalization (drawing conclusions) in Sociology Learning for Students of Class XI IPS 1 State Senior High School 1 Foreman. The problem in this study in general is "How to Implement the Discovery Learning Model in Sociology Learning for Students of Class XI IPS 1 for Public High School 1 foreman?". Data collection techniques using observation, interviews and documentation studies. Primary data sources are obtained directly through interviews that have been conducted between researchers and informants. The informants are sociology teachers. Secondary data sources are sources of data indirectly obtained by researchers from their sources. So this study looks at archives or documents owned by sociology teachers such as student learning outcomes data and sociology teacher teaching materials. The results of research and analysis carried out by researchers showed that the results of this study run in accordance with the concept of the application of discovery learning learning models carried out to students which consists of: stimulation, problem statements, data collection, data processing, verification and generalization.